2016
DOI: 10.1111/vcp.12372
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacterial contamination andDNAquantification in stored blood units in 2 veterinary hospital blood banks

Abstract: Blood transfusions in veterinary medicine have become increasingly more common and are now an integral part of lifesaving and advanced treatment in small and large animals. Important risks associated with transfusion of blood products include the transmission of various infectious diseases. Several guidelines suggest what infectious agents to screen for in canine and feline transfusion medicine. However, while the risk of bacterial contamination of blood products during storage and administration has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…and Pseudomona spp. have been described in feline WB and pRBC units using open collection systems, and one pRBC unit collected with a semi-closed system was tested positive to Pseudomonas fluorescens after color changes were noted [ 60 , 61 ]. Moreover, two studies performed blood cultures in feline pRBC collected with open systems, testing 10 feline pRBC at day 32 of storage in one study and 6 units at day 42 of storage on the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Pseudomona spp. have been described in feline WB and pRBC units using open collection systems, and one pRBC unit collected with a semi-closed system was tested positive to Pseudomonas fluorescens after color changes were noted [ 60 , 61 ]. Moreover, two studies performed blood cultures in feline pRBC collected with open systems, testing 10 feline pRBC at day 32 of storage in one study and 6 units at day 42 of storage on the other.…”
Section: Discussionmentioning
confidence: 99%
“…However, no units showed signs of bacterial growth (e.g. dark purple to black or green discoloration) or visible signs of clotting or fibrin in the blood bag at any time during storage, although the absence of these indicators does not preclude de possibility of bacterial contamination [ 61 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Brecher and Hay (2005), the contamination of blood bags may originate from normal skin flora, since it is very difficult to totally disinfect human skin and make it aseptic, being even more difficult in domestic animals (Stefanetti et al, 2016). In addition, the donor asymptomatic bacteremia at the time of donation or infections during the incubation or convalescence period, which are not reported by the custodian during the clinical screening, may also be the cause of contamination (Fonseca et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, no marked visible color change, hemolysis, or clots were noted in any WB unit (either those administered to recipients or those not transfused) or in any segments during the period of storages. In our previous study, we showed that the bacterial load associated with a color change in blood bags during their shelf lives ranged from 1.18 × 10 7 to 5.22 × 10 8 GE/mL, suggesting that a gross color change can be observed with this extent of bacterial contamination. However, a color change is not always evident when contamination occurs, and this method is not sufficiently sensitive to detect contaminants present in lower quantities …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of transfusion‐associated sepsis involves psychrophilic bacteria capable of growth at refrigeration temperatures, including the Gram‐negative contaminants Pseudomonas spp. and Serratia spp., which have been implicated in blood bag contamination . A study has shown that when blood units were inoculated with 1–10 cfu/mL of S. liquefaciens and stored at 4°C, concentrations of 10 9 cfu/mL were reached after 14 days in storage .…”
Section: Discussionmentioning
confidence: 99%